EUROPEAN EXPERIENCES OF CORPORATE SOCIAL RESPONSIBILITY IN THE PHARMACEUTICAL INDUSTRY - Vasko Naumovski, Milena Apostolovska Stepanoska, Milena Gosevska (Iksad Global, 2022)
Corporate social responsibility is the company's responsibility for the impact of its decisions and activities on society and the environment. This is achieved through transparent and ethical behavior that contributes to sustainable development and takes into account the expectations of stakeholders and is in line with international norms. Corporate social responsibility is a way of doing business. It is directly related to sustainable development requiring the company to look at its financial, social and environmental performance. The social responsibility of the company should be strategically integrated fully in the business process of the company, the supply chain, the products, as well as in the customer relations. The company's social responsibility is perfectly in line with the company's quest for easier market access, increased productivity or reduced operating costs. The authors of the paper first analyze the concept of corporate social responsibility. Here they review the legal framework of corporate social responsibility and then make a more substantial overview of corporate social responsibility in the pharmaceutical industry. This section also presents the ethics in the pharmaceutical industry as part of corporate social responsibility and corporate social responsibility. At the end, the authors present their findings from the research.
Keywords: Corporate social responsibility; Pharmaceutical Industry